Strengthening Elementary School Teacher Competence in the Development of Artificial Intelligence-Based Teaching Modules at the Kalisongo Elementary School Cluster - Candra Utama; Esti Untari; Santy Dinar Permata (Abdi Masyarakat, 2026)
Strengthening Elementary School Teachers' Competence in Developing Artificial Intelligence-Based Teaching Modules in the Kalisongo Elementary School Cluster. The rapid diffusion of generative artificial intelligence requires elementary school teachers to use digital tools not only as content generators, but also as pedagogical supports that must be critically verified and aligned with students' needs. This community service program aimed to strengthen teachers' competence in developing AI-based teaching modules in the Kalisongo Elementary School Cluster, Dau District, Malang Regency. The program was implemented through training, guided practice, mentoring, and reflective evaluation. Evaluation data were collected using participant questionnaires, observation, documentation, and product-oriented reflection. The questionnaire generated 24 responses. The results showed that 79.2% of respondents considered the training materials very useful, 70.8% considered them very relevant to teachers' needs, 91.6% rated the training methods as effective or very effective, and 66.7% reported being highly motivated to develop AI-based teaching modules after the training. The overall benefit of the program was rated very useful by 83.3% of respondents. These findings indicate that contextual, practice-oriented AI training can strengthen teachers' readiness to design teaching modules while maintaining pedagogical control over AI-generated outputs. Follow-up mentoring is needed to validate the modules and examine their classroom impact.